Novel exploration of Raman microscopy and non-linear optical imaging in adenomyosis - Shen, Zhuowei; He, Yingying; Shen, Zhuoyi; Wang, Xuefei; Wang, Yang; Hua, Zhengyu; Jiang, Nan; Song, Zejiang; Li, Rui; Xiao, Zhen (Frontiers in Medicine, 2022)
Background Adenomyosis is a common gynecological disease in women. A relevant literature search found that approximately 82% of patients with adenomyosis chose to undergo hysterectomy. However, women of childbearing age are more likely to undergo surgery to preserve the uterus. Because it is difficult to determine the extent of adenomyosis, it is almost impossible to resect adenomyotic tissue and retain the uterus at the same time. Materials and methods Following ethics approval and patient consent, tissue samples were resected and prepared to create frozen slices for analysis. One slice was subjected to H&E staining while the remaining slices were photographed with Coherent Anti-Stokes Raman Scattering (CARS), Second-Harmonic Generation (SHG) microscopy, and Raman spectroscopy. Comparative observations and analyses at the same positions were carried out to explore the diagnostic ability of CARS, SHG, and Raman spectroscopy for adenomyosis. Results In adenomyotic tissue, we found two characteristic peaks at 1,155 and 1,519 cm–1 in the Raman spectrum, which were significantly different from normal tissue. The substances shown in the CARS spectrum were represented by peaks of 1,519 cm–1. SHG microscopy showed a distribution of collagen at the focus of the adenomyosis. Conclusion This study represents a novel analysis of Raman microscopy, CARS, and SHG in the analysis of adenomyotic lesions. We found the diffraction spectrum useful in determining the focal boundary and the diagnosis of adenomyosis in the tested samples.